Understanding Information Seeking Behaviors in Specialized Agricultural Contexts: The Tutur Apple Farming Case - Suryaman Sule; Hidayat, Kliwon; Purnomo, Mangku; Cahyono, Edi Dwi (HABITAT, 2025)
Apple farming in the Tutur region faces adaptation challenges due to climate change, environmental degradation, and limited access to information. This study highlights the importance of contextual understanding of farmers' information-seeking behaviour by integrating Social Learning (Bandura) and Community of Practice (Wenger) theories. This study examines how farmers seek, interpret, and disseminate information; the social context that shapes the learning process; and the supporting and inhibiting factors of the community information ecosystem. A qualitative approach with a case study design explored apple farmers' learning practices in depth. Data were obtained through interviews, observation, and documentation, and then analysed thematically with triangulation techniques for validity. Results show that farmers actively seek information through digital media, field experiments, and informal discussions. Learning occurs through observation, imitation, and social reinforcement, and is facilitated by a community of practice that encourages a culture of sharing. However, barriers such as closed-mindedness and institutional weaknesses are still found. This study emphasises the importance of participatory and community-based approaches in developing agricultural information systems. The findings are helpful for extension workers and policymakers to design interventions that are adaptive to farmers' social dynamics.